The laboratory astrophysics spectroscopy programme at Imperial College London - Belmonte,MT; Pickering,JC; Clear,CP; Mairey,FC; Liggins,F (Galaxies, 2018)
Accurate atomic parameters, such as transition probabilities, wavelengths, and energy levels, are indispensable for the analysis of stellar spectra and the obtainment of chemical abundances. However, the quantity and quality of the existing data in many cases lie far from the current needs of astronomers, creating an acute need for laboratory measurements of matching accuracy and completeness to exploit the full potential of the very expensively acquired astrophysical spectra. The Fourier Transform Spectrometer at Imperial College London works in the vacuum ultraviolet-visible region with a resolution of 2,000,000 at 200 nm. We can acquire calibrated spectra of neutral, singly, and doubly ionized species. We collaborate with the National Institute of Standards and Technology (NIST) and the University of Lund to extend our measurements into the infrared region. The aim of this review is to explain the current capabilities of our experiment in an understandable way to bring the astronomy community closer to the field of laboratory astrophysics and encourage further dialogue between our laboratory and all those astronomers who need accurate atomic data. This exchange of ideas will help us to focus our efforts on the most urgently needed data.